2019
DOI: 10.1186/s40659-019-0268-x
|View full text |Cite
|
Sign up to set email alerts
|

RASAL1 induces to downregulate the SCD1, leading to suppression of cell proliferation in colon cancer via LXRα/SREBP1c pathway

Abstract: BackgroundRecent studies have confirmed that RASAL1 has an antitumor effect in many cancers, but its functional role and the molecular mechanism underlying in colon cancer has not been investigated.ResultsWe collected human colon cancer tissues and adjacent non-tumor tissues, human colon cancer cell lines LoVo, CaCo2, SW1116, SW480 and HCT-116, and normal colonic mucosa cell line NCM460. RT-qPCR was used to detect the RASAL1 level in the clinical tissues and cell lines. In LoVo and HCT-116, RASAL1 was artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Liver X receptor α (LXRα), as a member of the nuclear receptor family, plays an important role in glucose metabolism and inflammatory response, 11 and in recent years, a study has found its important role in the development and progression of tumors. For example, one study found that regulation of the LXRα pathway could suppress the proliferation of colon cancer cells, 12 and one other study pointed out that the LXRα pathway may be related to apoptosis of BCCs promoted by 7-ketocholesterol. 11 However, there is no study on the relationship between PRMT5 and LXRα yet.…”
Section: Introductionmentioning
confidence: 99%
“…Liver X receptor α (LXRα), as a member of the nuclear receptor family, plays an important role in glucose metabolism and inflammatory response, 11 and in recent years, a study has found its important role in the development and progression of tumors. For example, one study found that regulation of the LXRα pathway could suppress the proliferation of colon cancer cells, 12 and one other study pointed out that the LXRα pathway may be related to apoptosis of BCCs promoted by 7-ketocholesterol. 11 However, there is no study on the relationship between PRMT5 and LXRα yet.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 It is generally believed that SREBP1 an upstream regulatory protein in the tumor lipid metabolism pathway, and most clinical studies 28 have assessed compounds that induce insulin_related genes and SREBP cleavage-activating protein, as well as affecting the synthesis of downstream cholesterol, 29,30 and even targeting ACLY as the first key substrate enzyme of DNL. 31,32 ACLY and SREBP1 are also key factors connecting glucose metabolism and lipid metabolism. 33 The significance of SREBP1 and ACLY in tumor lipid metabolism is relatively clear, and knocking down both genes aimed to refine the study of tumor lipid metabolism and find more suitable therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…RASAL1(RAS protein activator like 1) is a member of the RAS GTPase-activating protein (GAP) family ( 39 ), which participates in cellular proliferation and differentiation and is associated with pulmonary fibrosis ( 40 ), and cancer ( 41 ). A recent study showed that lncRNAPCAT29 inhibits pulmonary fibrosis via downregulating RASAL1/ERK1/2 signal pathway, which suppresses the expression levels of MMP2 and MMP9 in alveolar epithelial cells and pulmonary fibroblast cell differentiation ( 40 ).…”
Section: Discussionmentioning
confidence: 99%